Mix Design Programming for Normal Concrete using Cubic Equation - Yudhistira Baggio, Eugene; Hartono Bagio, Toni; Tistogondo, Julistyana (Universitas Ibn Khaldun Bogor, 2023)
A computer programming requires inputs and processes to produce output, good data processing requires a formula, in programming when using tables is very inefficient, so an approach is needed in this case the existing table tables are converted into formulas, making it easier to process programming. Mix Design for normal concrete, in general, always use tables that have SNI (ACI), the tables are modified with Polynomial Regression to be equations, tables in SNI (ACI) that are transformed into equations. The equation produced, using polynomial regression, with a value of R² â‰ˆ 1. The equation to find weight of mixing water (Ww) = y1j, y2j, with main variable aggregate maximum, additional variables are slump, the second equation is volume air content (VAC) = y3i, additional variables are exposures, water cement ratio (WCR) = y4i, with aggregate maximum variables, while additional variables are air requirements in concrete (non-air entrained/air entrained),weight of coarse aggregate (WCA) = y5i, with two variables aggregate maximum and FM (Finest Modulus), and initial estimates of fresh concrete weight (WFC) = y6i